A new species of the thorid shrimp genus Heptacarpus Holmes, 1900 (Decapoda: Caridea) from Japan - Komai, Tomoyuki (Zootaxa, 2025)
The thorid shrimp genus Heptacarpus Holmes, 1900 is currently represented by 34 species (De Grave & Fransen 2011; Komai 2023; DecaNet 2025). These species are exclusively found in the North Pacific, inhabiting various environments from coastal waters to the continental slope, reaching depths of up to 1580 m (Hayashi 1979; Butler 1980; Wicksten 1990; Komai & Ivanov 2008; Komai & Komatsu 2009). From East Asian waters, 16 species have been recorded, of which 13 species are restricted to the area (Hayashi 1979, 1992; Hayashi & Chiba 1987, 1989; Komai & Ivanov 2008; Kim 2012; Xu & Li 2015; Komai 2023).During a study of material dredged from the coastal waters south of Izu Peninsula, central Japan, two specimens somewhat resembling Heptacarpus geniculatus (Stimpson, 1860) and H. longirostris (Kobjakova, 1936), were found. Through a combination of morphological comparison and phylogenetic analysis utilizing the mitochondrial 16S rRNA gene, the study uncovered a previously unknown species. Here the new species, H. elatus, is described and illustrated.